2019
DOI: 10.1108/jmd-04-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in the safety sense: where does perceived organisational support fit?

Abstract: Purpose The purpose of this paper is to examine leaders’ influence on the safety behaviours of employees and the possible mediating role of perceived organisational support (POS), focussing on transformational and transactional leadership. Design/methodology/approach Data were gathered through a survey from 264 engineers and technicians in the power transmission subsector in Ghana and analysed using structural equation modelling. Findings The analyses revealed that transformational leadership influenced sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…The current results revealed that transformational leadership style has a positive impact on SCBs in the PDS. Consistent with the views of Addo and Dartey-Baah (2019), managers who exhibit a transformational leadership style can influence employees to oblige and demonstrate safety behaviors beyond the regular safety expectation of top management. Though past research on the subject matter is scanty, a few safety experts examining safety leadership within the power and energy sector have also reiterated the point that transformational leaders and managers are capable of promoting SCBs if they can set a vision and strategic direction, empower, provide resources and constantly emphasize and reinforce the importance of safety to employees beyond their normal obligations (Martínez-Córcoles et al , 2011; Martínez-Córcoles et al , 2011; Martínez-Córcoles et al , 2013; Martínez-Córcoles et al , 2012).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The current results revealed that transformational leadership style has a positive impact on SCBs in the PDS. Consistent with the views of Addo and Dartey-Baah (2019), managers who exhibit a transformational leadership style can influence employees to oblige and demonstrate safety behaviors beyond the regular safety expectation of top management. Though past research on the subject matter is scanty, a few safety experts examining safety leadership within the power and energy sector have also reiterated the point that transformational leaders and managers are capable of promoting SCBs if they can set a vision and strategic direction, empower, provide resources and constantly emphasize and reinforce the importance of safety to employees beyond their normal obligations (Martínez-Córcoles et al , 2011; Martínez-Córcoles et al , 2011; Martínez-Córcoles et al , 2013; Martínez-Córcoles et al , 2012).…”
Section: Discussionmentioning
confidence: 88%
“…However, earlier research has been inconsistent regarding the role of transactional leaders in employee safety behaviors in the power and energy sector. While Addo and Dartey-Baah (2019) argued that transactional leaders or managers have no influence on employee safety behaviors, Kivimaki et al (1995) were of the view that certain transactional leadership practices such as providing communication and feedback to subordinates can help foster appropriate safety behaviors. Moreover, the traditional view of transactional leadership is that rewards and punishments may not produce and achieve expected results in the long term (Bass, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective leadership is considered as sine qua non for successful organizational management irrespective of nature of business, industry and national contexts (Addo and Dartey-Baah, 2019; Amin et al , 2017; Cummings et al , 2018; Hanges et al , 2016). The positive effects of perceived “good” leadership styles (Banks et al , 2017; Inceoglu et al , 2018; Keskes et al , 2018; Wang et al , 2018) as well as the negative impacts of perceived “bad” or “dark” leadership styles (Kim et al , 2019; Mackey et al , 2018; Milosevic et al , 2019) on managerial effectiveness and organizational performance are well documented in empirical research.…”
Section: Introductionmentioning
confidence: 99%